Emisi Gas Rumah Kaca dan Pemanasan Global - Abdullah Abdullah (Biocelebes, 2009)
The greenhouse effect was increased averaged of earth temperature 1-5°C when the increasing tendency of greenhouse gases is not reduce, it will causing of global warming increasing in 1,5 - 4,5°C on 2030. Increasing of solar radiation that reflecting from earth surface that absorbed by atmosphere will occur when the CO2 concentration rise in atmosphere. The extreme climate changes will disturb function of forest and another ecosystem, it will reduce their ability to absorbed CO2 gases from atmosphere. The global warming can effects ice melts. When ice melts, land or open water takes its place. Both land and open water are on average less reflective than ice and thus absorb more solar radiation. This causes more warming, which in turn causes more melting, and this cycle continues. Finally, the sea level rise will give a very big effect to island country. Key words: Greenhouse effect, global warming